1991
DOI: 10.9746/sicetr1965.27.64
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Estimation of the Time Delay in Continuous-Time Systems

Abstract: Estimation of the Time Delay in Continuous-Time Systems•õ The identification of time delays in continuous-time systems is considered, and a simple recursive algorithm is derived with the use of Newton's method. Consistency properties of the algorithm are analyzed using the ordinary differential equation approach. It is shown that the algorithm leads to the true, unique solution if a ramp input is used. The algorithm is also applicable to the identification of timevarying delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As in Section 2, the computational processes of both estimators ( 31)-( 32) and ( 33)-(35) terminate on the basis of the observed stagnation in the minimisation criterion (28), exactly…”
Section: La Estimatorsmentioning
confidence: 99%
“…As in Section 2, the computational processes of both estimators ( 31)-( 32) and ( 33)-(35) terminate on the basis of the observed stagnation in the minimisation criterion (28), exactly…”
Section: La Estimatorsmentioning
confidence: 99%
“…Chen and Zhang 12) determined the time delay in the Auto-Regressive Moving Average (ARMA) model to minimize the cost function. In Zhao and Sagara, 13) the time delay in the ARMA model was determined so that the cost function was minimized using Newton's method. Fukuda et al 9) reported a method for estimating the time delay in the measured ultrasonic receiver outputs using cross-correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Among existing methods of identification of delay systems, a solution employing the gradient search algorithm for minimization of an auxiliary quality function is worth noticing (Zhao and Sagara, 1991). Also a three-stage procedure involving a preliminary guess of the delay, estimation of parameters and final identification of the delay can be functional (Kozłowski and Kowalczuk, 2009).…”
Section: Parameter and Delay Estimationmentioning
confidence: 99%
“…Identification of such delays along with the parameters of the continuous models is definitely a challenging issue. Among the existing solutions, off-line estimation of input delay based on the gradient search can be applied (Ferretti et al, 1991;Zhao and Sagara, 1991). A dedicated three-stage procedure for off-line identification of delay can be used in practical implementations (Kozłowski and Kowalczuk, 2009).…”
Section: Introductionmentioning
confidence: 99%